Children and School-based Research: 'informed consent' or 'educated consent'? - David, Miriam; Edwards, Rosalind; Alldred, Pam (British Educational Research Journal, 2001)
This article discusses 'informed consent' in relation to research with children and young people in educational settings. In particular, it reflects upon issues that arose in the process of gaining their active consent to participate in the authors' research on children's understandings of parental involvement in education. In line with contemporary approaches to research with children, the children were provided with 'information' through leaflets and classroom activities in order for them to make 'choices' about participation. On reflection, these methods can be seen as distinctly educational, in that they drew on liberal education discourses and on practices adopted in 'progressive' British schooling. The children and young people's responses to the consent processes must be seen in the context of the authors' implicit use of broadly pedagogic approaches, and of the research taking place in a school setting inscribed with differential power relations. The authors therefore interrogate the concept of 'informed consent' that is employed in research, and its prior construction of 'information'. This raises questions about distinctions between providing information and teaching, and implications for conducting ethical social research with children.
Keywords: parents; résultat de recherche; utilisation des recherches; éducation prioritaire